Coincident velocity map image reconstruction illustrated by the single-photon valence photoionisation of CF3SF5. Issue 44 (6th November 2017) - Bodi, Andras; Hemberger, Patrick; Tuckett, Richard P.
Abstract : Photoion–photoelectron kinetic energy and angular anisotropy correlation maps reveal new details about the ionization mechanism. Abstract : Velocity map imaging offers high energy resolution and collection efficiency of the steady flux of photoelectrons and ions in continuous photoionisation experiments. In this proof-of-principle work, we show by the photoionisation of trifluoromethyl sulphur pentafluoride, CF3 SF5, that the four-dimensional problem of reconstructing coincident velocity map images of electrons and ions of certain mass can be addressed by separating the energy distribution from the angular anisotropy. The energy spectrum is predominantly determined by the radial distribution of the image, whereas laboratory frame angular anisotropies are revealed based on the radial distribution of the image multiplied with a 2nd-degree Legendre polynomial. The reconstruction yields the energy correlation between the photoion and the photoelectron characteristic of the photoelectron spectrum and the kinetic energy release. The angular anisotropy β -parameter maps of the photoelectrons and photoions are also obtained as 2D functions of the electron and ion kinetic energies. For photoionisation of CF3 SF5, the energy correlation reveals suprastatistical kinetic energy release (KER) in CF3 + production in the ground cationic X̃ + state, but statistical KER in the excited Ã + and B̃ + state bands. Although the photoelectron distribution is isotropic, the photoion anisotropy in the energy range of the X̃ + state speaks for prompt dissociation after preferential ionisation of CF3 SF5 molecules aligned with the polarisation vector of the synchrotron radiation. The angular dependence of the photoionisation cross section is confirmed by ab initio calculations for vertical ionisation.